Alternativas tecnológicas para o uso sustentável de madeiras da Caatinga em cercas do semiárido do baixo São Francisco - Nogueira Júnior, Francisco de Carvalho (2017)
In the scope of this study, a interdisciplinarity approach was sought for sustainable practices in the construction of fences and conservation with native species. The objectives of this work were to uncover the preferences of the rural owners of the Paulo Afonso-BA region, as well as the native species used in the construction of their dead fences and qualitatively evaluate the state of conservation of these woods. The interdisciplinary methodology allowed the discovery of the use of 8 species of wood being an exotic, The two species preferred by the rural producers, Braúna, Schinopsis brasiliensis Engl. Native species, and Algaroba, Prosopis julifora (Sw) DC, an exotic species from the Peruvian semi - arid and invasive of the NEB Caatinga. The scarcity of the native species in the fences, however, was verified through the process of replacing the native cuttings by the use of the cuttings of the exotic Algaroba. We evaluated interdisciplinary dendroecological, anatomical and technological aspects (physical and chemical) in the stage of living and dead wood (stakes) in order to validate the state of conservation of dead wood, and adaptive survival strategies and their responses to climatic conditions in Living wood. The results obtained for the anatomical, physical and chemical study of the state of biodegradation of the cuttings, indicated exhaustion of the native species used in the fences. The current stage of conservation of the fences compromises the native species, due to the imminent need for substitution of these stakes, suggesting immediate management of the P. juliflora species. The construction of chronologies of growth rings of these two species allowed to evaluate locally the influence of the climate of the region on its growth in the Caatinga, from the evaluation of different local environmental variables and global climatic events for ENSO and TSA. The chronology of P. juliflora occurred between the period 1975-2015, with an inter-correlation of 0.531 and an average annual rate of increase of 3.71 mm, while the chronology of S. brasiliensis occurred between 1963-2015, with inter- Correlation of 0.560, and mean annual rate of increase of 3.33 mm. P. juliflora showed a correlation with annual precipitation (52%), autumn / winter rainy season (0.57) and thunderstorms (0.35), being inversely correlated with mean temperature (-0.47), Maximum temperature (-0.31) and insolation (-0.43). The growth of S. brasiliensis showed a correlation with annual precipitation (0.71), rainy season autumn / winter (0.64), humidity (0.39) and thunderstorms (0.46), being inversely correlated with temperature Of the air (average: -0.59, maximum: -0.41), insolation (-0.51) and evaporation (-0.35). The conclusions reached were that the P. juliflora species, since its introduction in the mid-1960s, have expanded their living area by favoring them as a function of local climatic conditions and the action of the anthropic degradation processes of the Caatinga through the withdrawal of their Which is leading to scarcity of native species. On the other hand, the low cost of the P. juliflora cuttings, wood technologically resistant to biodegradation has enabled the process of native wood substitution. From the ecological and conservation point of view, mitigating measures of control of this exotic species are necessary.